Suporte a Alertas de Emergência na TV 3.0 Brasileira - Costa, Richelieu R. A.; Omaia, Derzu; Araújo, Tiago M. U.; Pereira, Jóison O.; Cruz, Miguel P. S.; Barbosa, Matheus M.; Toscano, Rafael; L. S. Filho, Guido (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2024)
The TV 3.0 project is under development, managed by the Forum of the Brazilian Digital Terrestrial TV System (SBTVD), with the participation of researchers from academia and industry. There was a Call for Proposals for this development, resulting in 36 responses from 21 organizations worldwide. The proposals were evaluated and examined, and the SBTVD Forum forwarded its recommendations on selecting candidate technologies to the Brazilian Ministry of Communications. Currently, some researchers are working on elaborating specifications for video encoding, audio encoding, subtitles, and emergency warnings, among others. This work analyzed the emergency warning requirements for warnings with glosses and audio description media. We proposed and developed a solution for these requirements, involving the extension of the CCWS server API and a system architecture implemented as a proof of concept.